123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191192193194195196197198199200201202203204205206207208209210211212213214215216217218219220221222223224225226227228229230231232233234235236237238239240241242243244245246247248249250251252253254255256257258259260261262263264265266267268269270271272273274275276277278279280281282283284285286287288289290291292293294295296297298299300301302303304305306307308309310311312313314315316317318319320321322323324325326327328329330331332333334335336337338339340341342343344345346347348349350351 |
- from sympy.core.expr import unchanged
- from sympy.core.mul import Mul
- from sympy.core.numbers import (I, Rational as R, pi)
- from sympy.core.power import Pow
- from sympy.core.singleton import S
- from sympy.core.symbol import Symbol
- from sympy.functions.elementary.exponential import (exp, log)
- from sympy.functions.elementary.miscellaneous import sqrt
- from sympy.functions.elementary.trigonometric import (cos, sin)
- from sympy.series.order import O
- from sympy.simplify.radsimp import expand_numer
- from sympy.core.function import expand, expand_multinomial, expand_power_base
- from sympy.testing.pytest import raises
- from sympy.core.random import verify_numerically
- from sympy.abc import x, y, z
- def test_expand_no_log():
- assert (
- (1 + log(x**4))**2).expand(log=False) == 1 + 2*log(x**4) + log(x**4)**2
- assert ((1 + log(x**4))*(1 + log(x**3))).expand(
- log=False) == 1 + log(x**4) + log(x**3) + log(x**4)*log(x**3)
- def test_expand_no_multinomial():
- assert ((1 + x)*(1 + (1 + x)**4)).expand(multinomial=False) == \
- 1 + x + (1 + x)**4 + x*(1 + x)**4
- def test_expand_negative_integer_powers():
- expr = (x + y)**(-2)
- assert expr.expand() == 1 / (2*x*y + x**2 + y**2)
- assert expr.expand(multinomial=False) == (x + y)**(-2)
- expr = (x + y)**(-3)
- assert expr.expand() == 1 / (3*x*x*y + 3*x*y*y + x**3 + y**3)
- assert expr.expand(multinomial=False) == (x + y)**(-3)
- expr = (x + y)**(2) * (x + y)**(-4)
- assert expr.expand() == 1 / (2*x*y + x**2 + y**2)
- assert expr.expand(multinomial=False) == (x + y)**(-2)
- def test_expand_non_commutative():
- A = Symbol('A', commutative=False)
- B = Symbol('B', commutative=False)
- C = Symbol('C', commutative=False)
- a = Symbol('a')
- b = Symbol('b')
- i = Symbol('i', integer=True)
- n = Symbol('n', negative=True)
- m = Symbol('m', negative=True)
- p = Symbol('p', polar=True)
- np = Symbol('p', polar=False)
- assert (C*(A + B)).expand() == C*A + C*B
- assert (C*(A + B)).expand() != A*C + B*C
- assert ((A + B)**2).expand() == A**2 + A*B + B*A + B**2
- assert ((A + B)**3).expand() == (A**2*B + B**2*A + A*B**2 + B*A**2 +
- A**3 + B**3 + A*B*A + B*A*B)
- # issue 6219
- assert ((a*A*B*A**-1)**2).expand() == a**2*A*B**2/A
- # Note that (a*A*B*A**-1)**2 is automatically converted to a**2*(A*B*A**-1)**2
- assert ((a*A*B*A**-1)**2).expand(deep=False) == a**2*(A*B*A**-1)**2
- assert ((a*A*B*A**-1)**2).expand() == a**2*(A*B**2*A**-1)
- assert ((a*A*B*A**-1)**2).expand(force=True) == a**2*A*B**2*A**(-1)
- assert ((a*A*B)**2).expand() == a**2*A*B*A*B
- assert ((a*A)**2).expand() == a**2*A**2
- assert ((a*A*B)**i).expand() == a**i*(A*B)**i
- assert ((a*A*(B*(A*B/A)**2))**i).expand() == a**i*(A*B*A*B**2/A)**i
- # issue 6558
- assert (A*B*(A*B)**-1).expand() == 1
- assert ((a*A)**i).expand() == a**i*A**i
- assert ((a*A*B*A**-1)**3).expand() == a**3*A*B**3/A
- assert ((a*A*B*A*B/A)**3).expand() == \
- a**3*A*B*(A*B**2)*(A*B**2)*A*B*A**(-1)
- assert ((a*A*B*A*B/A)**-2).expand() == \
- A*B**-1*A**-1*B**-2*A**-1*B**-1*A**-1/a**2
- assert ((a*b*A*B*A**-1)**i).expand() == a**i*b**i*(A*B/A)**i
- assert ((a*(a*b)**i)**i).expand() == a**i*a**(i**2)*b**(i**2)
- e = Pow(Mul(a, 1/a, A, B, evaluate=False), S(2), evaluate=False)
- assert e.expand() == A*B*A*B
- assert sqrt(a*(A*b)**i).expand() == sqrt(a*b**i*A**i)
- assert (sqrt(-a)**a).expand() == sqrt(-a)**a
- assert expand((-2*n)**(i/3)) == 2**(i/3)*(-n)**(i/3)
- assert expand((-2*n*m)**(i/a)) == (-2)**(i/a)*(-n)**(i/a)*(-m)**(i/a)
- assert expand((-2*a*p)**b) == 2**b*p**b*(-a)**b
- assert expand((-2*a*np)**b) == 2**b*(-a*np)**b
- assert expand(sqrt(A*B)) == sqrt(A*B)
- assert expand(sqrt(-2*a*b)) == sqrt(2)*sqrt(-a*b)
- def test_expand_radicals():
- a = (x + y)**R(1, 2)
- assert (a**1).expand() == a
- assert (a**3).expand() == x*a + y*a
- assert (a**5).expand() == x**2*a + 2*x*y*a + y**2*a
- assert (1/a**1).expand() == 1/a
- assert (1/a**3).expand() == 1/(x*a + y*a)
- assert (1/a**5).expand() == 1/(x**2*a + 2*x*y*a + y**2*a)
- a = (x + y)**R(1, 3)
- assert (a**1).expand() == a
- assert (a**2).expand() == a**2
- assert (a**4).expand() == x*a + y*a
- assert (a**5).expand() == x*a**2 + y*a**2
- assert (a**7).expand() == x**2*a + 2*x*y*a + y**2*a
- def test_expand_modulus():
- assert ((x + y)**11).expand(modulus=11) == x**11 + y**11
- assert ((x + sqrt(2)*y)**11).expand(modulus=11) == x**11 + 10*sqrt(2)*y**11
- assert (x + y/2).expand(modulus=1) == y/2
- raises(ValueError, lambda: ((x + y)**11).expand(modulus=0))
- raises(ValueError, lambda: ((x + y)**11).expand(modulus=x))
- def test_issue_5743():
- assert (x*sqrt(
- x + y)*(1 + sqrt(x + y))).expand() == x**2 + x*y + x*sqrt(x + y)
- assert (x*sqrt(
- x + y)*(1 + x*sqrt(x + y))).expand() == x**3 + x**2*y + x*sqrt(x + y)
- def test_expand_frac():
- assert expand((x + y)*y/x/(x + 1), frac=True) == \
- (x*y + y**2)/(x**2 + x)
- assert expand((x + y)*y/x/(x + 1), numer=True) == \
- (x*y + y**2)/(x*(x + 1))
- assert expand((x + y)*y/x/(x + 1), denom=True) == \
- y*(x + y)/(x**2 + x)
- eq = (x + 1)**2/y
- assert expand_numer(eq, multinomial=False) == eq
- def test_issue_6121():
- eq = -I*exp(-3*I*pi/4)/(4*pi**(S(3)/2)*sqrt(x))
- assert eq.expand(complex=True) # does not give oo recursion
- eq = -I*exp(-3*I*pi/4)/(4*pi**(R(3, 2))*sqrt(x))
- assert eq.expand(complex=True) # does not give oo recursion
- def test_expand_power_base():
- assert expand_power_base((x*y*z)**4) == x**4*y**4*z**4
- assert expand_power_base((x*y*z)**x).is_Pow
- assert expand_power_base((x*y*z)**x, force=True) == x**x*y**x*z**x
- assert expand_power_base((x*(y*z)**2)**3) == x**3*y**6*z**6
- assert expand_power_base((sin((x*y)**2)*y)**z).is_Pow
- assert expand_power_base(
- (sin((x*y)**2)*y)**z, force=True) == sin((x*y)**2)**z*y**z
- assert expand_power_base(
- (sin((x*y)**2)*y)**z, deep=True) == (sin(x**2*y**2)*y)**z
- assert expand_power_base(exp(x)**2) == exp(2*x)
- assert expand_power_base((exp(x)*exp(y))**2) == exp(2*x)*exp(2*y)
- assert expand_power_base(
- (exp((x*y)**z)*exp(y))**2) == exp(2*(x*y)**z)*exp(2*y)
- assert expand_power_base((exp((x*y)**z)*exp(
- y))**2, deep=True, force=True) == exp(2*x**z*y**z)*exp(2*y)
- assert expand_power_base((exp(x)*exp(y))**z).is_Pow
- assert expand_power_base(
- (exp(x)*exp(y))**z, force=True) == exp(x)**z*exp(y)**z
- def test_expand_arit():
- a = Symbol("a")
- b = Symbol("b", positive=True)
- c = Symbol("c")
- p = R(5)
- e = (a + b)*c
- assert e == c*(a + b)
- assert (e.expand() - a*c - b*c) == R(0)
- e = (a + b)*(a + b)
- assert e == (a + b)**2
- assert e.expand() == 2*a*b + a**2 + b**2
- e = (a + b)*(a + b)**R(2)
- assert e == (a + b)**3
- assert e.expand() == 3*b*a**2 + 3*a*b**2 + a**3 + b**3
- assert e.expand() == 3*b*a**2 + 3*a*b**2 + a**3 + b**3
- e = (a + b)*(a + c)*(b + c)
- assert e == (a + c)*(a + b)*(b + c)
- assert e.expand() == 2*a*b*c + b*a**2 + c*a**2 + b*c**2 + a*c**2 + c*b**2 + a*b**2
- e = (a + R(1))**p
- assert e == (1 + a)**5
- assert e.expand() == 1 + 5*a + 10*a**2 + 10*a**3 + 5*a**4 + a**5
- e = (a + b + c)*(a + c + p)
- assert e == (5 + a + c)*(a + b + c)
- assert e.expand() == 5*a + 5*b + 5*c + 2*a*c + b*c + a*b + a**2 + c**2
- x = Symbol("x")
- s = exp(x*x) - 1
- e = s.nseries(x, 0, 6)/x**2
- assert e.expand() == 1 + x**2/2 + O(x**4)
- e = (x*(y + z))**(x*(y + z))*(x + y)
- assert e.expand(power_exp=False, power_base=False) == x*(x*y + x*
- z)**(x*y + x*z) + y*(x*y + x*z)**(x*y + x*z)
- assert e.expand(power_exp=False, power_base=False, deep=False) == x* \
- (x*(y + z))**(x*(y + z)) + y*(x*(y + z))**(x*(y + z))
- e = x * (x + (y + 1)**2)
- assert e.expand(deep=False) == x**2 + x*(y + 1)**2
- e = (x*(y + z))**z
- assert e.expand(power_base=True, mul=True, deep=True) in [x**z*(y +
- z)**z, (x*y + x*z)**z]
- assert ((2*y)**z).expand() == 2**z*y**z
- p = Symbol('p', positive=True)
- assert sqrt(-x).expand().is_Pow
- assert sqrt(-x).expand(force=True) == I*sqrt(x)
- assert ((2*y*p)**z).expand() == 2**z*p**z*y**z
- assert ((2*y*p*x)**z).expand() == 2**z*p**z*(x*y)**z
- assert ((2*y*p*x)**z).expand(force=True) == 2**z*p**z*x**z*y**z
- assert ((2*y*p*-pi)**z).expand() == 2**z*pi**z*p**z*(-y)**z
- assert ((2*y*p*-pi*x)**z).expand() == 2**z*pi**z*p**z*(-x*y)**z
- n = Symbol('n', negative=True)
- m = Symbol('m', negative=True)
- assert ((-2*x*y*n)**z).expand() == 2**z*(-n)**z*(x*y)**z
- assert ((-2*x*y*n*m)**z).expand() == 2**z*(-m)**z*(-n)**z*(-x*y)**z
- # issue 5482
- assert sqrt(-2*x*n) == sqrt(2)*sqrt(-n)*sqrt(x)
- # issue 5605 (2)
- assert (cos(x + y)**2).expand(trig=True) in [
- (-sin(x)*sin(y) + cos(x)*cos(y))**2,
- sin(x)**2*sin(y)**2 - 2*sin(x)*sin(y)*cos(x)*cos(y) + cos(x)**2*cos(y)**2
- ]
- # Check that this isn't too slow
- x = Symbol('x')
- W = 1
- for i in range(1, 21):
- W = W * (x - i)
- W = W.expand()
- assert W.has(-1672280820*x**15)
- def test_expand_mul():
- # part of issue 20597
- e = Mul(2, 3, evaluate=False)
- assert e.expand() == 6
- e = Mul(2, 3, 1/x, evaluate = False)
- assert e.expand() == 6/x
- e = Mul(2, R(1, 3), evaluate=False)
- assert e.expand() == R(2, 3)
- def test_power_expand():
- """Test for Pow.expand()"""
- a = Symbol('a')
- b = Symbol('b')
- p = (a + b)**2
- assert p.expand() == a**2 + b**2 + 2*a*b
- p = (1 + 2*(1 + a))**2
- assert p.expand() == 9 + 4*(a**2) + 12*a
- p = 2**(a + b)
- assert p.expand() == 2**a*2**b
- A = Symbol('A', commutative=False)
- B = Symbol('B', commutative=False)
- assert (2**(A + B)).expand() == 2**(A + B)
- assert (A**(a + b)).expand() != A**(a + b)
- def test_issues_5919_6830():
- # issue 5919
- n = -1 + 1/x
- z = n/x/(-n)**2 - 1/n/x
- assert expand(z) == 1/(x**2 - 2*x + 1) - 1/(x - 2 + 1/x) - 1/(-x + 1)
- # issue 6830
- p = (1 + x)**2
- assert expand_multinomial((1 + x*p)**2) == (
- x**2*(x**4 + 4*x**3 + 6*x**2 + 4*x + 1) + 2*x*(x**2 + 2*x + 1) + 1)
- assert expand_multinomial((1 + (y + x)*p)**2) == (
- 2*((x + y)*(x**2 + 2*x + 1)) + (x**2 + 2*x*y + y**2)*
- (x**4 + 4*x**3 + 6*x**2 + 4*x + 1) + 1)
- A = Symbol('A', commutative=False)
- p = (1 + A)**2
- assert expand_multinomial((1 + x*p)**2) == (
- x**2*(1 + 4*A + 6*A**2 + 4*A**3 + A**4) + 2*x*(1 + 2*A + A**2) + 1)
- assert expand_multinomial((1 + (y + x)*p)**2) == (
- (x + y)*(1 + 2*A + A**2)*2 + (x**2 + 2*x*y + y**2)*
- (1 + 4*A + 6*A**2 + 4*A**3 + A**4) + 1)
- assert expand_multinomial((1 + (y + x)*p)**3) == (
- (x + y)*(1 + 2*A + A**2)*3 + (x**2 + 2*x*y + y**2)*(1 + 4*A +
- 6*A**2 + 4*A**3 + A**4)*3 + (x**3 + 3*x**2*y + 3*x*y**2 + y**3)*(1 + 6*A
- + 15*A**2 + 20*A**3 + 15*A**4 + 6*A**5 + A**6) + 1)
- # unevaluate powers
- eq = (Pow((x + 1)*((A + 1)**2), 2, evaluate=False))
- # - in this case the base is not an Add so no further
- # expansion is done
- assert expand_multinomial(eq) == \
- (x**2 + 2*x + 1)*(1 + 4*A + 6*A**2 + 4*A**3 + A**4)
- # - but here, the expanded base *is* an Add so it gets expanded
- eq = (Pow(((A + 1)**2), 2, evaluate=False))
- assert expand_multinomial(eq) == 1 + 4*A + 6*A**2 + 4*A**3 + A**4
- # coverage
- def ok(a, b, n):
- e = (a + I*b)**n
- return verify_numerically(e, expand_multinomial(e))
- for a in [2, S.Half]:
- for b in [3, R(1, 3)]:
- for n in range(2, 6):
- assert ok(a, b, n)
- assert expand_multinomial((x + 1 + O(z))**2) == \
- 1 + 2*x + x**2 + O(z)
- assert expand_multinomial((x + 1 + O(z))**3) == \
- 1 + 3*x + 3*x**2 + x**3 + O(z)
- assert expand_multinomial(3**(x + y + 3)) == 27*3**(x + y)
- def test_expand_log():
- t = Symbol('t', positive=True)
- # after first expansion, -2*log(2) + log(4); then 0 after second
- assert expand(log(t**2) - log(t**2/4) - 2*log(2)) == 0
- def test_issue_23952():
- assert (x**(y + z)).expand(force=True) == x**y*x**z
- one = Symbol('1', integer=True, prime=True, odd=True, positive=True)
- two = Symbol('2', integer=True, prime=True, even=True)
- e = two - one
- for b in (0, x):
- # 0**e = 0, 0**-e = zoo; but if expanded then nan
- assert unchanged(Pow, b, e) # power_exp
- assert unchanged(Pow, b, -e) # power_exp
- assert unchanged(Pow, b, y - x) # power_exp
- assert unchanged(Pow, b, 3 - x) # multinomial
- assert (b**e).expand().is_Pow # power_exp
- assert (b**-e).expand().is_Pow # power_exp
- assert (b**(y - x)).expand().is_Pow # power_exp
- assert (b**(3 - x)).expand().is_Pow # multinomial
- nn1 = Symbol('nn1', nonnegative=True)
- nn2 = Symbol('nn2', nonnegative=True)
- nn3 = Symbol('nn3', nonnegative=True)
- assert (x**(nn1 + nn2)).expand() == x**nn1*x**nn2
- assert (x**(-nn1 - nn2)).expand() == x**-nn1*x**-nn2
- assert unchanged(Pow, x, nn1 + nn2 - nn3)
- assert unchanged(Pow, x, 1 + nn2 - nn3)
- assert unchanged(Pow, x, nn1 - nn2)
- assert unchanged(Pow, x, 1 - nn2)
- assert unchanged(Pow, x, -1 + nn2)
|